HIF-3α-Induced miR-630 Expression Promotes Cancer Hallmarks in Cervical Cancer Cells by Forming a Positive Feedback Loop - Qiaohui Gao; Zhenghua Ren; Shengyuan Jiao; Juan Guo; Xia Miao; Jin Wang; Junye Liu (Journal of Immunology Research)
Purpose. Hypoxia has crucial functions in the development and metastasis of cervical cancer by inducing the expression of numerous genes, including microRNA genes. But we know little about how the hypoxia factors and microRNAs orchestrate to regulate hallmarks of cervical cancer cells. Methods. We conducted RNA sequencing (RNA-seq) and chromatin immunoprecipitation sequencing (ChIP-seq) experiments to investigate the targets of HIF-3α or miR-630. ChIP-qPCR and RT-qPCR were carried out to validate the results of ChIP-seq and RNA-seq. Cellular, molecular, and radiation experiments were conducted to explore the functions of miR-630. Results. In this study, we showed that hypoxia-induced overexpression of HIF-3α increased the expression of dozens of miRNAs, including miR-630. Hypoxia could also directly induce miR-630 expression. ChIP-seq data showed that HIF-3α activates miR-630 expression by directly binding to the promoter of its host gene. Meanwhile, stable overexpression of miR-630 increased the expression of HIF-3α, but repressed the expression of HIF-1α, indicating a positive feedback loop between HIF-3α and miR-630. Consequently, stable overexpression of miR-630 in HeLa cells promotes cancer hallmarks, including radioresistance, inhibition of apoptosis, increased migration and invasion, and EMT-mediated metastasis. Meanwhile, inhibition of miR-630 showed opposite features. Conclusion. Taken together, our findings indicate a novel hypoxia-induced HIF-3α and miR-630 regulatory feedback loop contributing to metastasis and progression of cervical cancer cells and suggest that HIF-3α and miR-630 might act as potential biomarkers and therapeutic targets for cervical cancer in the future.